(untitled) (CIPEEX, 2025)
INTRODUCTION: Dry eye syndrome (DES) is a multifactorial condition marked by chronic inflammation of the lacrimal functional unit and loss of tear film stability, leading to impaired function. Recent studies have found higher levels of vitamin D in tear fluid from lacrimal and accessory glands compared to plasma, and vitamin D receptors have been identified in corneal and retinal tissues, enhancing the corneal epithelial barrier. OBJECTIVE: To investigate the relationship between vitamin D deficiency, dry eye, and impaired tear function. METHOD: This integrative review followed the PICo strategy, utilizing the databases Biblioteca Virtual em Saúde (BVS), PubMed, and Google Scholar. The search terms included ’Vitamin D,’ ’Dry Eye Syndromes,’ and ’Lacrimal Elimination,’ with the Boolean operator ’AND.’ Articles published in Portuguese and English over the last 10 years were analyzed, resulting in five selected studies. RESULTS: Studies demonstrated significantly lower levels of vitamin D in tear fluid of DES patients compared to controls. Tear Break-Up Time (TBUT), a measure of tear film stability, correlated with serum 25(OH)D levels. TBUT was shorter in vitamin D-deficient individuals than in those with sufficient levels. CONCLUSION: Vitamin D status is correlated with DES, potentially regulating tear secretion in the lacrimal glands through similar mechanisms. Supplementation may be beneficial for treating DES.